Introducing electric field to porous fins for analyzing maximum energy transport and minimum entropy generation: Accurateness analysis - Balaram Kundu; Se-Jin Yook (Case Studies in Thermal Engineering)
The presented analysis includes the electric and magnetic fields for energy transfer, unlike previous studies that only focussed on the magnetic field. The irreversibility aspects are highlighted in porous fins to evaluate entropy generation. Predicted results highlight that individual external electric and magnetic fields have a significant potential to enhance the thermal performance parameters of a porous fin. At this design point, the porosity also plays a vital role in the same purpose, and the improvement of design aspects is noticed compared to the solid fin. The proposed optimization process in the first law maximizes the energy transfer, whereas it diminishes the entropy generation in the second law under a constraint material volume. But, the irreversible diffusion energy transfer in a porous fin has significantly dominated the factors associated with the energy transfer enhancement. Therefore, this study predicts that the entropy generation has not the lowest value at the maximum energy transport circumstance analyzed by both the first and second laws. This study demonstrates that the possibilities of incrementing maximum heat transfer and fin effectiveness are 129.84 % and 193.46 %, respectively. However, there is no significant change in the fin efficiency at the extremum heat transfer conditions.